Barriers to Third Mission: Organizational and individual antecedents - Gloria Naranjo-Africano; Jaider Vega-Jurado; Liney Manjarres-Henríquez (Journal of Innovation and Entrepreneurship, 2023)
The fulfillment of the University's Third Mission has led the university to become a key actor for social and economic development in its regions of influence through a much closer linkage with the different agents in its environment. Thus, the literature has highlighted both the benefits derived from the Third University Mission, the difficulties inherent in the process and the existence of various barriers that can hinder its consolidation in the academic environment. Within the framework of these studies, it has been possible to identify three types of barriers to adopting the third mission: process, researcher, and ally or partner. It is worth mentioning that most of the research developed to date has focused on the study of the impact of the barriers on the development of the Third Mission but not on the analysis of the factors that can influence or attenuate the perception of these barriers. This is surprising if one considers that identifying these factors is relevant in designing strategies to promote the University's Third Mission. Therefore, this article aims to identify the factors that influence or attenuate the researcher's perception of different types of barriers to developing Third Mission activities. The study was based on data from a survey applied to a sample of academics categorized in the National System of Science, Technology and Innovation of Colombia and linked to 6 higher education institutions in the Colombian Caribbean region. Binary logistic regression models were established to analyze the data obtained. The results obtained suggest that, in addition to the researcher's previous experience in the external sector, their perception of the existence of processes or support services provided by the university for the promotion of relationships with actors in the socioeconomic environment is important to mitigate the barriers perceived during the development of Third Mission activities, especially when these activities are located in the support for the management and execution of technology transfer activities. In particular, it was found that as the academic's perception of the policies and procedures, support activities, and the university's technology transfer capacity improves, the barriers of both the researcher and those associated with the process are dissipated. This implies that universities should advance in the institutionalization of the third mission and in strengthening the functions of promotion, advice and support, as well as promotion structures and thus be able to mitigate the perceived barriers to the development of the University's Third Mission.
Keywords: 650; Barriers; Organizational aspects; Researcher characteristics; Stokes quadrant; Third Mission